EDUKASI PENCEGAHAN HIPERTENSI PADA MASYARAKAT DI DESA KLASEMAN - Syazana Zahra Umardi; Ariana Candra Dewi; Syalwa Fitria Wurandhani; Trijaya; Awalia Nurfitria Khoirunnisa; Mauliddina Adinda Putri Indah Pakerti; Fahrizal Sidiq Radiasto; Silvi Puspitasari; Nur Aeni Afiyah Fauziah; Viona Putri Giwani; Rahma Annisa; Nabila Jaiza Mawarni; Adnan Faris Naufal; Yuli Kusumawati (Universitas Muhammadiyah Surakarta, 2025)
Hypertension is a global health problem with a high prevalence in the elderly population. This condition can increase the risk of serious complications such as heart disease, stroke, and kidney failure. Prevention of hypertension through proper health education is crucial to maintain quality of life and independence. This activity seeks to evaluate the effectiveness of the hypertension prevention education program by increasing knowledge in fit elderly. The method used is a lecture with poster media. The pre-test and post-test were conducted with a 10-item questionnaire and involved 55 participants from various age groups in Klaseman Village, Gatak District, Sukoharjo Regency. The educational intervention included delivering material on the importance of a healthy diet (low salt, high fiber), regular physical activity, stress management, and self-monitoring of blood pressure or regular health checks. The results of the activity showed that after the intervention, there was a significant increase in the level of knowledge. This indicates that a structured and comprehensive education program is effective in empowering fit elderly to adopt a healthy lifestyle and reduce the risk of hypertension.